Sudut Pandang Penulis Berita BBC Terhadap Perilaku Prabowo: Penilaian Sikap Analisis - Yolanda, Chornelia Chelsa; Riris Mutiara Paulina Simamora (e-LinguaTera, 2024)
This research investigates how international media portray Prabowo's image, due to his personal branding during the election process, which has garnered public attention. Prabowo, a former military general with a controversial past, has been dubbed 'cuddly grandpa' by the youth. This study aims to analyze the attitude of BBC News authors towards Prabowo using Martin & White (2005) language appraisal analysis, specifically focusing on the attitude subsystems of affect, judgment, and appreciation. A qualitative descriptive approach was employed, the researcher gathering the data from BBC News articles discussing the Indonesian election from February to March 2024. Nine relevant articles were identified on this platform. The researchers transcribed the data into word form and utilized the AntConc corpus software to identify sentences that contains the word ‘Prabowo,’ then the researchers categorized each sentence into attitude subsystem affect, judgment, and appreciation. The findings reveal that "judgment," with a total of 69 instances, was the most prevalent attitude. This was followed by "appreciation" with 32 instances and "affect" with 19 instances. Negative polarity was the most commonly used, appearing 67 times, while positive polarity was used 58 times. The distribution of polarity within each attitude subsystem is as follows: "affect" featured 5 positive and 14 negative polarity; "judgment" had 22 positive and 47 negative polarity; and "appreciation" showed 30 positive and 2 negative polarity. The authors effectively influenced readers by critically portraying Prabowo in their coverage. Despite this critical portrayal, they still acknowledged Prabowo's positive behavior and achievements through expressions of appreciation. Based on these results, the researchers concluded that BBC News articles were not biased in favor of Prabowo.